Distance-induced changes in walking speed after stroke: Relationship to community walking activity - Awad, Louis N. (J Neurol Phys Ther, 2019)
BACKGROUND AND PURPOSE: Physical inactivity is a major contributing factor to reduced health and quality of life. The total distance walked during the 6-minute walk test is a strong indicator of real world walking activity after stroke. The purpose of this study was to determine if measurement of distance-induced changes in walking speed during the 6-minute walk test improves the test’s ability to predict community walking activity. METHODS: For 40 individuals poststroke, community walking activity (steps/day), the total distance walked during the 6-minute walk test (6MWT(total)), and the difference between the distances walked during the final and first minutes of the test (Δ6MWT(min6–min1)) were analyzed using moderated regression. Self-efficacy, assessed using the Activities-specific Balance Confidence (ABC) scale, was also included in the model. RESULTS: Alone, 6MWT(total) explained 41% of the variance in steps/day. The addition of Δ6MWT(min6–min1) increased explanatory power by 29% (ΔR(2)=0.29, p<0.001). The final model accounted for 71% of steps/day variance (F((4,32))=19.52, p<0.001). Examination of a significant 6MWT(total) × Δ6MWT(min6–min1) interaction revealed a positive relationship between 6MWT(total) and steps/day, with individuals whose distances declined from minute 1 to minute 6 by 0.10m/s or more presenting with substantially less steps/day than those whose distances did not decline. DISCUSSION AND CONCLUSIONS: Co-assessment of distance-induced changes in walking speed during the 6-minute walk test and the total distance walked substantially improves the prediction of real world walking activity after stroke. This study provides new insight into how walking ability after stroke can be characterized to reduce heterogeneity and advance personalized treatments.